Regulation of Jasmonate-Mediated Stamen Development and Seed Production by a bHLH-MYB Complex in Arabidopsis. Issue 6 (22nd May 2015) - Qi, Tiancong; Huang, Huang; Song, Susheng; Xie, Daoxin
Abstract : MYC5 is a target of JAZs and functions redundantly with MYC2, MYC3, and MYC4 to regulate stamen development and seed production via interactions with the MYB transcription factors MYB21 and MYB24. Abstract: Stamens are the plant male reproductive organs essential for plant fertility. Proper development of stamens is modulated by environmental cues and endogenous hormone signals. Deficiencies in biosynthesis or perception of the phytohormone jasmonate (JA ) attenuate stamen development, disrupt male fertility, and abolish seed production in Arabidopsis thaliana . This study revealed that JA -mediated stamen development and seed production are regulated by a bHLH-MYB complex. The IIIe basic helix-loop-helix (bHLH ) transcription factor MYC5 acts as a target of JAZ repressors to function redundantly with other IIIe bHLH factors such as MYC2, MYC3, and MYC4 in the regulation of stamen development and seed production. The myc2 myc3 myc4 myc5 quadruple mutant exhibits obvious defects in stamen development and significant reduction in seed production. Moreover, these IIIe bHLH factors interact with the MYB transcription factors MYB21 and MYB24 to form a bHLH-MYB transcription complex and cooperatively regulate stamen development. We speculate that the JAZ proteins repress the bHLH-MYB complex to suppress stamen development and seed production, while JA induces JAZ degradation and releases the bHLH-MYB complex to subsequently activate the expression of downstream genes essential for stamen development and seed production.